THE PORTRAIT OF DEPRESSION SEEN THROUGH METAPHOR IN WILFRED OWENâ€™S â€œDISABLEDâ€ - Aprin Kusumaning Wardani; Eko Budi Setiawan (Humaniora Scientia, 2017)
This research is discussed â€œDisabledâ€ poem dealing with depression that happened in the speaker condition between his past and future in Wilfred Owenâ€™s â€œDisabledâ€. It Â focusees onÂ  Â two major purposes: (1) to find out, to classifies, and describe Â the Â metaphor Â as Â seen Â through Â in Â Wilfred Â Owenâ€™s Â â€œDisabledâ€. Â (2) Â to understand the symbol that reveals depression in Wilfred Owenâ€™s â€œDisabledâ€. This research is used written data. The data and the theories were taken from written form and internet browsing. In this study, the researcher used some theories. They were of figure of speech, metaphor, symbol, and depression. Furthermore, the Â approaches were used structural approach, formalistic approach, and psychological approach. The approaches were applied to determine the approach in analyzing the metaphor and symbol found in poem. There were two metaphors related to depression, physical depressionÂ  Â andÂ  Â psychologicalÂ  Â depression.Â  Â PhysicalÂ  Â depressionÂ  Â describedÂ  Â the speakerâ€™s Â condition Â and Â situation Â whichÂ  Â causeÂ  Â the Â depression. Â Psychological depression Â was Â the Â effect Â of Â his Â disability. Â Moreover, Â there Â were Â two Â symbols revealing depression namely disappointment and death. Â  Keywords: Metaphor, Irony, Symbol, Depression